ANTESEDEN DAN KONSEKUENSI MORAL PAJAK (Studi Pada Wajib Pajak Orang Pribadi di Kota Pekanbaru) - Yesi Mutia Basri; Al Azhar Al Azhar (Universitas Pakuan, 2017)
This study aims to examine socio-demographic factors (age, gender, and education), personal financial experience and political attitudes as a moral determinant of individual tax payers. This study also examines the consequences of tax morale that is tax evasion. This study uses 100 samples of individual tax payers registered in KPP Pratama Tampan Pekanbaru. By using regression analysis, the results showed that socio demographic factors, i.e. age, gender and education, did not affect the tax morale and employment status, furthermore as an entrepreneur also has no effect on tax morale. However, trust and satisfaction on democracy and politics affect tax morale. In addition, tax moral also affect the behavior of tax evasion.Keywords: age, gender, education, income, entrepreneurship, satisfaction, trust, tax morale, tax fraud